2023
DOI: 10.1021/acsapm.3c00917
|View full text |Cite
|
Sign up to set email alerts
|

Melamine-Based Nanocomposites for Selective Dopamine and Uric Acid Sensing

Abstract: The formation process of carbon dots (CDs) is mostly polymerization; recently, studies on the polymerization of carbon families (graphene oxide and C60) have been receiving exciting attention. Herein, a protocol of prepolymerization and electropolymerization of monomer (melamine) and nanomonomer (CDs fixed melamine residues) was proposed to prepare a nanocomposite for selective dopamine (DA) and uric acid (UA) sensing. The nanomonomer was prepared by hydrothermal prepolymerization of melamine, and then the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Table 3 compares the analytical characteristics of our sensor with those electrochemical sensors based on CNTs for the simultaneous quantification of Do and UA published since 2021 [58][59][60][61][62][63][64][65][66][67]. Among them, Liao et al [60] reported detection limits for Do and UA comparable and higher to our sensor, respectively; Rattanaumpa et al [63] presented detection limits higher and comparable than our sensor for Do and UA, respectively, while Li et al [66] reported comparable detection limits to our sensor for both compounds.…”
Section: Simultaneous Detection Of Do and Ua In The Presence Of Aamentioning
confidence: 55%
“…Table 3 compares the analytical characteristics of our sensor with those electrochemical sensors based on CNTs for the simultaneous quantification of Do and UA published since 2021 [58][59][60][61][62][63][64][65][66][67]. Among them, Liao et al [60] reported detection limits for Do and UA comparable and higher to our sensor, respectively; Rattanaumpa et al [63] presented detection limits higher and comparable than our sensor for Do and UA, respectively, while Li et al [66] reported comparable detection limits to our sensor for both compounds.…”
Section: Simultaneous Detection Of Do and Ua In The Presence Of Aamentioning
confidence: 55%
“…The relative standard deviation (RSD) of the redox peak current of the PA ox/SPCE is 1.96% and 1.60% (Fig. 5f), 40,41 respectively, so it is feasible to use electrodeposited PA ox as an internal reference probe.…”
Section: Resultsmentioning
confidence: 99%
“…5E-G. The Randles-Sevcik formula, eqn (1), was used to calculate the active specific surface area of the electrode: 51,52 I p = 2.69 Â 10 5 n 3/2 AD 1/2 v 1/2 C 0 (1) where in n is the number of transfer electrons, A (cm 2 ) is the active specific surface area, D (cm 2 s À1 ) is related to the diffusion coefficient, v (V s À1 ) is the scan rate and C 0 (mol cm À3 ) is the concentration of [Fe(CN) 6 ] 3À/4À . When the electrolyte solution is 0.1 M KCl containing 5 mM [Fe(CN) 6 ] 3À/4À , n =1 and D = 6.20 Â 10 À6 (cm 2 s À1 ), then it can be calculated from eqn (1) that the active specific surface area of the SPCE is 0.0735 cm 2 , the MWCNTs/ SPCE is 0.0824 cm 2 and the FC-MWCNTs/SPCE is 0.112 cm 2 (Fig.…”
Section: Characterization Of the Sensormentioning
confidence: 99%
“…7F is a schematic diagram of the principle of adsorption detection. 51,54 The two slopes of the linear relationship between the two sections can be interpreted as single-layer adsorption followed by multi-layer adsorption, resulting in a decrease in the amplitude of the current. Fig.…”
Section: Electrochemical Detection Of Nicmentioning
confidence: 99%